Moünier-Kuhn Syndrome: a case report - Barbosa Pinto Rodrigues, Iago (2020)
Introduction: Tracheobroncomegaly or Mounier-Kuhn syndrome is a rare disease, mainly observed in middle-aged men before the 5th decade of life, characterized by atrophy or absence of elastic fibers or smooth muscles of the trachea wall and main bronchi. dilation of these structures. Weakness of connective tissue, associated with inhalation of air pollutants and cigarette smoke, is believed to be the major factors in the development of this syndrome. Diagnosis may be occasional in asymptomatic individuals, but often with recurrent respiratory infections and bronchiectasis. DESCRIPTION: A.H.A.G., 65, male, single, white. Reported chronic cough with increased frequency 10 days ago associated with an increase in sputum, currently greenish. He also complained of uncontrolled daily irregular fever, dyspnea on exertion, and night sweats. Patient mentions a diagnosis of bronchiectasis, but has not adhered to HRT ambulatory follow-up since 2015. CONCLUSION: Mounier-Kuhn syndrome is characterized by increased diameter of the trachea and main bronchi associated with reduced mucociliary clearance, which leads to the individual to develop respiratory infections frequently. The diagnosis is made by chest CT. The treatment is only performed in the symptomatic, aiming to treat the triggering factor of decompensation